2019
DOI: 10.1002/pa.1995
|View full text |Cite
|
Sign up to set email alerts
|

Anomie at public organizations: How can the quality of work life help?

Abstract: Will enhancing the quality of work life impact the reduction of anomic behaviors at work in public sector organizations? To answer this question, we examined the impact of three structural, managerial, and social dimensions of the quality of work life, including the employees' anomie behaviors at the workplace. A cross‐sectional survey data were collected from 250 employees working in the public sector organizations located in the Kerman Province, (southeast) Iran. Our findings support the negative effects tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Accordingly, anomie at work emerged as one of the underlying mechanisms explaining the relationship between organizational fairness and both the emotional exhaustion and leave intentions of precarious workers. Along similar lines, using survey-based data from 250 public sector workers in Iran, Jahanshahi and Dehghani [28] found that enhancing the quality of work life can reduce anomic behaviors at work. As a consequence, according to Choi et al [27], anomie at the workplace can increase deviant workplace behavior.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Accordingly, anomie at work emerged as one of the underlying mechanisms explaining the relationship between organizational fairness and both the emotional exhaustion and leave intentions of precarious workers. Along similar lines, using survey-based data from 250 public sector workers in Iran, Jahanshahi and Dehghani [28] found that enhancing the quality of work life can reduce anomic behaviors at work. As a consequence, according to Choi et al [27], anomie at the workplace can increase deviant workplace behavior.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have shown that employees' engagement in such deviant behaviors is less frequent in a workplace with low levels of anomie [27]. Increasing the quality of work life in the workplace is an important way of deterring the anomic behavior of employees [28]. According to the study in the context of public sector organizations, fair wages, rewards, security, reduction of the gender pay gap, improvements to work happiness, and promotion and learning opportunities for all employees are some solutions that can reduce the level of normlessness or anomie at work.…”
Section: Anomie At Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Cullen et al (2004) states that managers' behaviors in terms of the concept of justice and ethics are in harmony with the organizational anomie. It has been found out that organizational culture, structure, management style, immoral behavior and unethical behavior in an organization increase employee anomaly (Jahanshahi & Dehghani, 2019;Sypniewska, 2017). Bass and Riggio (2006) in their study associating anomie and transformational leadership; they emphasized that the practices of transformational leaders are effective in gaining important goals, meanings and values that employees need and are related to anomia.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A research group of locally trained research assistants helped us throughout the data collection process(Jahanshahi & Bhattacharjee, ; Jahanshahi & Dehghani, ). To encourage participants and obtain their trust, we received and attached a supportive letter (Maktoob) from a local university to each survey questionnaire.…”
Section: Methodsmentioning
confidence: 99%